Correlation Between Magnitude of ST Segment Elevation and the Proximal Right Coronary Artery Lesion in Acute Inferior Myocardial Infarction (Bangladesh Heart Journal, 2024)
Introduction: The determination of the probable site of occlusion within RCA in acute inferior MI is very important because proximal occlusions are likely to cause greater myocardial damage and an early invasive strategy may be planned in such cases. Furthermore, identification of infarct-related artery and its site in acute inferior myocardial infarction not only guide decision regarding the urgency of revascularization but also guide to avoid therapy that may adversely affect the outcome.Objective: To predict the site of lesion in right coronary artery in acute inferior myocardial infarction by the magnitude of ST segment elevation in inferior leads (II, III and aVF).Methodology: This cross-sectional study was conducted in the Department of Cardiology, Sylhet MAG Osmani Medical College Hospital, from January 2014 to December 2015. A total of 50 consecutive patients with inferior MI who present within 12 hours of symptom onset and received fibrinolytic therapy were selected according to inclusion and exclusion criteria. Using 12-lead ECG, height of ST segment elevation in leads II, III and aVF were measured & coronary angiography(CAG) was performed during index hospital period .CAG which showed culprit lesion in RCA were only taken for the study. The sum of STsegment elevation in inferior leads were then correlated with the proximal lesion in RCA. Results: The age of the patients ranged from 31 to 70 years with the mean age of 51.1 (SD 9.2) years. Majorities (88%) of the patients were male and ratio of male to female was 7.33:1.Out of 50 patients, 26(52%) had the lesion in proximal, 19 (38%) in mid and 05 (10%) in distal RCA. Patients with proximal RCA lesion showed a mean ST segment elevation of 12.5(SD 1.07) mm, with mid RCA lesion 8.5 (SD 0.80) mm and distal RCA lesion 6.5(SD 0.42) mm. There was a positive correlation of sum of ST segment elevation in inferior leads II, III and aVF to the proximal lesion in RCA (r=0.923, P < 0.05).Conclusion: From the study it is concluded that the magnitude of ST segment elevation in inferior leads (II,III, aVF) can predict site of lesion in RCA in acute inferior wall myocardial infarction; the greater the sum of the height of ST segment elevation in inferior leads, the higher is the probability of lying the lesion in proximal right coronary artery.Bangladesh Heart Journal 2024; 39(1): 44-48